Simple Accurate Verification of Enthalpy‐Entropy Compensation and Isoequilibrium Relationship. Issue 17 (20th July 2021) - Griessen, Ronald; Dam, Bernard
Abstract: In many experimental investigations of thermodynamic equilibrium or kinetic properties of series of similar reactions it is found that the enthalpies and entropies derived from Van ′t Hoff or Arrhenius plots exhibit a strong linear correlation. The origin of this Enthalpy‐Entropy compensation, which is strongly related to the coalescence tendency of Van ′t Hoff or Arrhenius plots, is not necessarily due to a physical/chemical/biological process. It can also be a merely statistical artefact. A new method, called Combined K‐CQF makes it possible both to quantify the degree of coalescence of experimental Van 't Hoff lines and to verify whether or not the Enthalpy‐Entropy Compensation is of a statistical origin at a desired confidence level. The method is universal and can handle data sets with any degree of coalescence of Van 't Hoff (or Arrhenius) plots. The new method requires only a standard least square fit of the enthalpy ΔH versus entropy ΔS plot to determine the two essential dimensionless parameters K and CQF . The parameter K indicates the position (in inverse temperature) of the coalescence region of Van 't Hoff plots and CQF is a quantitative measure of the smallest spread of the Van 't Hoff plots. The position of the ( K, CQF ) couple with respect to universal confidence contours determined from a large number of simulations of random Van 't Hoff plots indicates straightforwardly whether or not the ΔH‐ΔS compensation is a statistical artefact. Abstract : Entropy‐Enthalpy compensation : Two dimensionless parameters K and CQF characterize quantitatively the coalescence of the Van't Hoff plots for similar reactions. K is related to the temperature at which the coalescence occurs and CQF is the Compensation Quality Factor, which is unity for perfect coalescence. By comparing measured ( K, CQF ) to universal confidence contours determined from a very large number of random simulations for N samples it is verified whether an Enthalpy‐Entropy Compensation is a real effect at a chosen confidence level. The same scheme is used for Arrhenius plots in kinetic studies.